Recent Advances in Molecular Pharmacology of the Histamine Systems: Organic Cation Transporters as a Histamine Transporter and Histamine Metabolism - Ogasawara Masahito; Yamauchi Kohei; Satoh Yoh-ichi; Yamaji Ryoichi; Inui Kenichi; Jonker Johan W.; Schinkel Alfred H.; Maeyama Kazutaka (Elsevier, 2006)
Abstract.: Histamine is inactivated by the histamine-metabolizing enzyme histamine N-methyl-transferase (HNMT) in bronchus, kidney, and the central nervous system. HNMT seems to be localized in the cytoplasm, but histamine is unable to easily enter the intracellular space. Therefore, two hypotheses can be elicited: one is the plasma membrane hypothesis that HNMT can be translocated to the plasma membrane and function at the cell surface under growth factor stimulation and the other is the transporter hypothesis that organic cation transporter (OCT)-2 and -3 can function as a histamine transporter as well. To investigate the involvement of OCT2, HEK293 cells stably double transfected with C-terminal hemagglutinin (HA)-tagged HNMT cDNA and/or C-terminal myc-tagged rat OCT2 were prepared for analysis of HNMT activity associated with OCT2 function. After 60-min incubation of these cells with PBS including HA (100 µM), Nτ-methylhistamine (MHA) concentration of the supernatants was determined by the HPLC-fluorometry method. MHA from cells with HNMT plus OCT-2 was produced at about 3-fold higher level than that from cells with HNMT alone, suggesting that OCT-2 could function as a histamine transporter as well and that HNMT function could partly depend on OCT-2 transporter activity. Using OCT-3 knockout (OCT-3−/−) mice, histamine content and survival rates were investigated in lipopolysaccharide (LPS)-induced endotoxemia model. Without LPS stimulation, histamine content was compared between OCT-3−/− and wild mice. Histamine content in the spleen of OCT-3−/− mice was higher than that of wild mice. With LPS stimulation, the survival rate of OCT-3−/− mice was significantly decreased 12 h after LPS (20 mg/kg) stimulation, suggesting that before immunological stimulation, a higher content of histamine in spleen could stimulate histamine receptors in mast cells, macrophages, dendritic cells, as well as T lymphocytes and explaining the decreased survival rate in OCT-3−/− mice possibly due to the functional changes of immunological cells. Keywords:: histamine N-methyltransferase, organic cation transporter